Basic Formulation of Instant Balinese Porridge Using a Gradual Dehydration Method: A Functional Food Approach Based on Balinese Local Wisdom - I Gusti Agung Yogi Rabani RS; Anak Agung Ngurah Dwi Ariesta Wijaya Putra; I Nyoman Arya Maha Putra (Jurnal Pijar MIPA, 2025)
The increasing demand for convenient foods has encouraged the development of instant products that not only offer practicality but also provide functional health benefits. Balinese porridge, traditionally prepared from red rice, coconut, and indigenous Balinese spices, represents a culturally valuable food with considerable nutritional potential. However, its conventional form is limited by a short shelf life and low practicality. This study aimed to evaluate the effect of drying temperature and drying duration on the physical, nutritional, sensory, and functional properties of instant Balinese porridge produced using a gradual dehydration method. A completely randomized factorial design was applied with two factors, namely drying temperature (50, 60, and 70 °C) and drying time (4, 6, and 8 h), resulting in nine treatment combinations with three replications. Gradual dehydration was conducted through initial oven drying followed by food dehydrator processing. The observed parameters included moisture content, rehydration time, proximate composition, sensory acceptance, and antioxidant activity expressed as IC50 values. The results demonstrated that drying at 60 °C for 6 h produced the lowest moisture content (5.1%) and the fastest rehydration time (2.8 min). The nutritional composition was dominated by carbohydrates (approximately 77%) and protein (7.6–8.3%), with a significant reduction in protein content observed at higher drying temperatures. Sensory evaluation indicated that the 60 °C–6 h treatment achieved the highest scores for color, aroma, taste, and overall acceptance. The highest antioxidant activity was also observed under this condition, with an IC50 value of 72.5 ppm. These findings confirm that gradual dehydration is an effective processing strategy for preserving the quality and functional properties of traditional Balinese porridge, highlighting its potential development as an instant functional food based on local wisdom.